Innovation, R&D efficiency and the impact of the regulatory environment: a two stage semi-parametric DEA approach - Astrid Cullmann; Jens Schmidt-Ehmcke; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper assesses the relative efficiency of knowledge production in the OECD using a nonparametric DEA approach. Resources allocated to R&D are limited and should therefore be used efficiently given the institutional and legal constraints. This paper presents efficiency scores based on an intertemporal frontier estimation for the period 1995 to 2004 and analyzes the impact of the regulatory environment using the single bootstrap procedure suggested by Simar and Wilson (2007). The empirical evidence supports the hypothesis that barriers to entry, aimed at reducing competition, lower research efficiency by attenuating the incentive to innovate and to allocate resources efficiently.
Keywords: C14; C24; L50; O31; O57; 330; R&D efficiency; data envelopment analysis; truncated regression; regulation; Wissen; Forschung; Technische Effizienz; Data-Envelopment-Analyse; Regulierung; OECD-Staaten